Unlocking Potential: Pentahelix Analysis of Stakeholder Roles in the Emerging Tourism Village - Baitulloh, Taqiy Gusdi; Endyana, Cipta; Pamungkas, Kasno; Putra, Adhika Graha Irianto (Jurnal Mamangan, 2025)
The development of tourism villages is a key strategy for local economic growth, yet many fail to progress beyond their initial designation due to a lack of stakeholder synergy. This study addresses this implementation gap by analyzing the roles and collaborative dynamics of stakeholders in Cilengkrang Village, a nascent tourism destination in Bandung Regency, Indonesia. Utilizing the Pentahelix framework—which comprises government, business, academia, community, and media—this research aims to diagnose the foundational barriers hindering its development. A qualitative descriptive method was employed, gathering data through in-depth interviews, passive participatory observation, and document analysis, which were then triangulated to ensure validity. The findings reveal a fractured collaborative framework where stakeholder roles are underdeveloped and poorly integrated. The government's top-down designation has not been matched by bottom-up community activation, evidenced by the absence of a formal Tourism Awareness Group (Pokdarwis). The business, academic, and media helices are found to be either disconnected from the tourism sector or entirely absent. This study concludes that this stagnation stems from a fundamental deficit in human resource capacity across all five nodes, specifically a lack of tourism-specific knowledge, collaborative skills, and entrepreneurial awareness. Therefore, the primary implication is that foundational human resource development, beginning with the government's facilitation of a community-based tourism institution, is the most critical prerequisite for unlocking the village's potential and building a functional, synergistic Pentahelix model.